Atypical presentation of neuromyelitis optica spectrum disorder: A diagnostic conundrum (Indian Journal of Case Reports, 2025)
Neuromyelitis optica spectrum disorder (NMOSD) is a relapsing, inflammatory demyelinating disorder of the central nervous system, most commonly presenting with optic neuritis and longitudinally extensive transverse myelitis. Diagnostic criteria rely on clinical features supported by aquaporin-4 (AQP4) antibody testing, but atypical presentations may occur, complicating recognition, especially in younger patients. We report the case of a 16-year-old female with congenital hypothyroidism and global developmental delay who presented with persistent vomiting, dysphagia, dysphonia, and vertigo. Clinical localization suggested brainstem involvement. Magnetic resonance imaging revealed lesions in the medulla extending into the cervicomedullary junction. Serum AQP4 antibody positivity confirmed NMOSD. The diagnosis was challenging due to the absence of optic neuritis and longitudinally extensive myelitis, and the patient’s young age. She improved significantly with corticosteroids and azathioprine. This case highlights the importance of considering NMOSD in atypical brainstem presentations in adolescents. Awareness of such variants, along with prompt antibody testing, is crucial for early initiation of immunotherapy and favorable outcomes.